Thoracic Gorham-Stout disease masquerading as an ovarian malignancy: a differential diagnosis in non-malignant causes of raised Ca-125 and overview of this rare pathology. Issue 11 (22nd November 2022) - Sattar, Alisha; Smyth, Sarah; Soleymani majd, Hooman
Abstract : Gorham-Stout disease (GSD) is thought to be due to uncontrolled proliferation of vascular and lymphatic structures within bone tissue causing destruction and osteolysis of bone. We present a patient in her mid-40s who reported chronic shoulder pain, a pleural effusion and irregular periods. Investigations showed osteolysis of her ribs, pleural effusions, an ovarian mass and a raised carbohydrate antigen 125 (Ca-125). She was subsequently diagnosed with GSD, and referred to gynaecology-oncology in consideration of potential ovarian malignancy. GSD is a diagnosis of exclusion that requires a high degree of clinical suspicion, as well as multiple investigations to achieve diagnosis. Clinicians rely on a small number of case reports to provide guidance for this. Therefore, this report provides an overview of a rare pathology, considers the differentials of a raised Ca-125 and describes how a pleural effusion, which links them both, alarmed us regarding an incidental finding of an ovarian cyst.